2022
DOI: 10.3390/ijms23105467
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Pituitary Adenylate Cyclase-Activating Peptide (PACAP) and Its Type 1 (PAC1) Receptor in Uterine Contractility during Endometritis in Pigs

Abstract: Uterine inflammation is a common pathology in animals, leading to disturbances in reproductive processes and reduced production profitability. Pituitary adenylate cyclase-activating peptide (PACAP) effects at the uterine level during inflammation are not known. In the current study, we analyzed the relative PACAP type 1 receptor (PAC1R) mRNA transcript and protein abundances in the myometrium (MYO), as well s PACAP and PAC1R involvement in the contractile function of inflamed pig uterus. To that end, E. coli s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…PAC1 receptor mRNA has been recently demonstrated in the uterus of healthy pigs, and the abundance of PAC1 receptor protein was reduced in inflammatory conditions ( 103 ). Endometrial inflammation also leads to changes in PACAP expression of the dorsal root ganglia supplying the porcine uterus ( 104 ).…”
Section: Pacap In the Uterus And Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…PAC1 receptor mRNA has been recently demonstrated in the uterus of healthy pigs, and the abundance of PAC1 receptor protein was reduced in inflammatory conditions ( 103 ). Endometrial inflammation also leads to changes in PACAP expression of the dorsal root ganglia supplying the porcine uterus ( 104 ).…”
Section: Pacap In the Uterus And Placentamentioning
confidence: 99%
“…There are only a few studies dealing with the actions of PACAP in the uterus and placenta. According to a recent study, PACAP treatment leads to decrease of amplitude and an increase in frequency of myometrium contraction in pigs ( 103 ). Effects of PACAP on blood vessels and smooth muscle contractility in the uteroplacental unit was also thoroughly investigated.…”
Section: Pacap In the Uterus And Placentamentioning
confidence: 99%
“…Several PACAPinduced intracellular pathways and signaling mechanisms were identified in cultured rat trigeminal ganglia primary sensory neurons related to cytokines, oxidative stress, and mitochondrial dysfunction, which are independent of the known and cloned PAC1 receptors [12]. Jana and co-workers described the role of PACAP in the inflamed pig uterus and showed that severe acute endometritis decreased PAC1 receptor expression in the myometrium, leading to decreased contractility [13].…”
mentioning
confidence: 99%